Redescription of Dardjilingia Yang (Hemiptera: Heteroptera: Pentatomidae) from India - Salini, S. (Zootaxa, 2016)
The genus Dardjilingia Yang, 1936 (Hemiptera: Pentatomidae: Pentatominae: Lestonocorini), comprising a single species, Dardjilingia nigriventris Yang, 1936, is redescribed and illustrated, including the descriptions of male and female genitalia for the first time. The genus Dardjilingia is removed from the present tribe Lestonocorini.